Exploring Australian regional cancer patients' experiences of clinical trial participation via telehealth. (August 2022) - Lee, Jin Joo; Burbury, Kate; Underhill, Craig; Harris, Samuel; Shackleton, Kylie; McBurnie, Jacquiline; McPhee, Narelle; Osmond, Felicity; Wilkins, Kathleen; Baden, Paul; Krishnasamy, Meinir
Introduction: Regional cancer patients face various barriers in accessing specialist cancer services. Teletrials are a new model of care that utilise communications technologies to enable access to and participation in clinical trials close to home. The present study aimed to explore the experiences of regional cancer patients and their carers while participating in a teletrial, and those of regional patients who travelled to a metropolitan centre for trial participation. Methods: A concurrent, mixed methods study design was used to address the study aim. Patient quality of life data were gathered for both groups and an audio-recorded semi-structured interview undertaken to explore patients' and carers' experiences of the two modes of trial participation. Greater weighting was given to the qualitative data. Results: Participants described teletrials as an acceptable and valuable initiative that reduced overall burden of trial participation. Irrespective of mode of delivery, patients and carers identified access to trials and specialist cancer services as an important equity issue for regional cancer patients. Discussion: From the perspective of regional cancer patients and carers, a teletrial offers convenient, acceptable access to a clinical trial. Although not all patients may want to engage in a teletrial, patients and carers agree that it offers equity of opportunity for trial participation, irrespective of where people live.